Rare Cause of Hip Pain: Transient Osteoporosis of the Hip-Two Case Reports - Senem Şaş; Fatmanur Aybala Koçak; Emine Eda Kurt; Hatice Rana Erdem; Figen Tuncay (Türk Osteoporoz Dergisi, 2015)
Transient osteoporosis of the hip (TOH) is a rare disease affecting especially middle-aged men and women in the third trimester of pregnancy with unknown etiology. It has a benign course with spontaneous resolution. Transient osteoporosis may be confused with other diseases such as avascular necrosis. Early diagnosis is important to identify and plan correct treatment. In this report, two male cases with complaint of hip pain and difficulty in walking, which were diagnosed with TOH was presented by reviewing current literature.